MULTILINGUAL CRISIS COMMUNICATION insights from china. - Li, Jia.; Zhang, Jie. ([S.l.] : ROUTLEDGE, 2025)
Multilingual Crisis Communication is the first book to explore the lived experiences of linguistic minorities in crisis-affected settings in the Global South, particularly during the Covid-19 pandemic. China has been selected as a case of inquiry for multilingual crisis communication because of its high level of linguistic diversity. Taking up critical sociopolitical approaches, this book conceptualizes multilingual crisis communication from three dimensions: identifying communication barriers, engaging communication repertoires, and empowering communication justice. Comprising eight main chapters, along with an introduction and an epilogue, this edited book is divided into three parts in terms of the demographic and social conditions of linguistic minorities, as indigenous, migrant, and those with communicative disabilities. This book brings together a range of critical perspectives of sociolinguistic scholars, language teachers, and public health workers. Each team of authors includes at least one member of the research community with many years of field work experience, and some of them belong to ethnic minorities. These studies can generate new insights for enhancing the accessibility and effectiveness of multilingual crisis communication. This book will be ofinterest to academics and postgraduate studentsin the fields ofmultilingualism, intercultural communication, translation and interpreting studies, and public health policy.
Keywords: Crisis management; Crisis management -- China; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Linguistics